2017
DOI: 10.1101/144667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological and transcriptomic evidence for ammonium induction of sexual reproduction inThalassiosira pseudonanaand other centric diatoms

Abstract: The reproductive strategy of diatoms includes asexual and sexual phases, but in many species, including the model centric diatom Thalassiosira pseudonana, sexual reproduction has never been observed. Furthermore, the environmental factors that trigger sexual reproduction in diatoms are not understood. Although genome sequences of a few diatoms are available, little is known about the molecular basis for sexual reproduction. Here we show that ammonium reliably induces the key sexual morphologies, including oogo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Phenomenologically, such a strategy can help reconcile observations of strongly species-dependent sinking events under favorable growth conditions, such as observed during NABE08. It is noteworthy here that, in the experimentally-triggered study on Thalassiosira pseudonana (Moore et al 2017), sexual reproduction was accompanied by a high level of TEP production (K.H. Halsey, personal observation).…”
Section: Accepted Articlementioning
confidence: 79%
See 2 more Smart Citations
“…Phenomenologically, such a strategy can help reconcile observations of strongly species-dependent sinking events under favorable growth conditions, such as observed during NABE08. It is noteworthy here that, in the experimentally-triggered study on Thalassiosira pseudonana (Moore et al 2017), sexual reproduction was accompanied by a high level of TEP production (K.H. Halsey, personal observation).…”
Section: Accepted Articlementioning
confidence: 79%
“…In other words, the evolution of physiological attributes that allow a given diatom species to sustain accelerations in division rate for a sufficient duration to achieve high concentrations may be based on improvements in sexual reproduction success that enhance genetic invention. If this is the case, then this advantage will be enhanced if sexual reproduction of a population is coordinated and especially if it is communicated or triggered once the population has achieved its critical density (Sterner and Elser 2002, Edlund and Stoermer 1997, Moore et al 2017. Recently, it was shown that sexual division in the diatom, Thalassiosira pseudonana, can be experimentally triggered by high concentrations of ammonium, but only after reaching maximal cell density (Moore et al 2017).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 78.2% of the genes in CiliaCut that were present in the diatom Thalassiosira pseudonana were present also in C. vulgaris 211/11P (Table S10): 84.2% of the T. pseudonana genes in MotileCut (genes in CiliaCut involved in motile flagella functions) were present also in C. vulgaris 211/11P. This result suggested that C. vulgaris 211/11P might be able to form gametes with motile flagella as previously observed for T. pseudonana during gametogenesis (Moore et al ., ).…”
Section: Resultsmentioning
confidence: 97%